2017
DOI: 10.1016/j.heares.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Damage to inner ear structure during cochlear implantation: Correlation between insertion force and radio-histological findings in temporal bone specimens

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 49 publications
3
55
0
Order By: Relevance
“…The disturbance in CM amplitude implies that there has been some interference with normal cochlear function, as may be caused by contact between the electrode and an intracochlear structure critical to hearing. For a straight cochlear implant electrode array, the vulnerable structures are the lateral cochlear wall and the basilar membrane 16 . All straight electrodes come into contact with one or both of these structures if inserted deeply enough 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance in CM amplitude implies that there has been some interference with normal cochlear function, as may be caused by contact between the electrode and an intracochlear structure critical to hearing. For a straight cochlear implant electrode array, the vulnerable structures are the lateral cochlear wall and the basilar membrane 16 . All straight electrodes come into contact with one or both of these structures if inserted deeply enough 17 .…”
Section: Discussionmentioning
confidence: 99%
“…De Seta et al found while testing the Flex28 on cadaveric model that the insertion force increased significantly as a function of depth of insertion both with traumatic and atraumatic insertions. The maximal peak forces occurred at the end of the insertion as a result of the friction between the entire array and the lateral cochlear wall and inner ear structures [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In each case of cochlear implantation an individual surgical approach is required. The key issue is to avoid the inner ear trauma and consequently to prevent apoptosis ( 48 ). Therefore the correct choice of electrode and its insertion depth is essential.…”
Section: Discussionmentioning
confidence: 99%